vivagham.com (e-Wedding) / Hemalatha Arumugam - Hemalatha, Arumugam (2004)
A wedding is the important event in a couple's life. To overcome problems that occur during the wedding preparations, a web based E-wedding system (Vivagham. Com) is developed to make the users to plan and budget their wedding in a very efficient way. In the meantime, this allows the customers to have more choices in same products like wedding costumes and enables to compare the prices in the same web page. The system is divided into two main modules, which are user and administrator. The aim of this project- Vivagham. Com is to develop and design the e-commerce application for a wedding preparation like selecting wedding costumes, invitation cards, caterer, hall booking and ordering system. This project also define the objective, scope, problem and tools to use that should be identified before the development of this system. Several research and analysis had done to do assessment and review about the system. Waterfall model with prototyping is used methodology of the proposed project. Three-tier client or server achitecture will be implemented to model the system architecture. In addition, Vivagham.com is planned to be developed by using Hypertext Processor (PHP)and Apache Web server on the Microsoft Window 2000 server platform utilizing database created using MySQL. The system design is dynamic and supporting concurrent users to interact with the system over internet. Finally, the intended E-wedding system should able to produce the web pages that allow users to do online shopping and order their desired products and services. A database also has to implemented for storing data that would be retrieved for display and captured from users.